2002
DOI: 10.5194/angeo-20-1647-2002
|View full text |Cite
|
Sign up to set email alerts
|

Velocities of auroral coherent echoes at 12 and 144 MHz

Abstract: Abstract. Two Doppler coherent radar systems are currently working at Hankasalmi, Finland, the STARE and CUTLASS radars operating at ∼ 144 MHz and ∼ 12 MHz, respectively. The STARE beam 3 is nearly co-located with the CUTLASS beam 5, providing an opportunity for echo velocity comparison along the same direction but at significantly different radar frequencies. In this study we consider an event when STARE radar echoes are detected at the same ranges as CUT-LASS radar echoes. The observations are complemented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 35 publications
(51 reference statements)
7
45
0
Order By: Relevance
“…Indeed, the electron density inside the polar cap arc can reach values of ∼2×10 5 cm −3 (Robinson et al, 1987), which is sufficient to strongly bend radio waves even at short ranges and large geometric aspect angles (e.g. Koustov et al, 2002). Additional argument for the above opinion comes from the elevation angle measurements presented on the bottom panel.…”
Section: Radar Observations In a Fixed Beammentioning
confidence: 89%
“…Indeed, the electron density inside the polar cap arc can reach values of ∼2×10 5 cm −3 (Robinson et al, 1987), which is sufficient to strongly bend radio waves even at short ranges and large geometric aspect angles (e.g. Koustov et al, 2002). Additional argument for the above opinion comes from the elevation angle measurements presented on the bottom panel.…”
Section: Radar Observations In a Fixed Beammentioning
confidence: 89%
“…In addition, there has been comparison of echo characteristics at widely differing frequencies, for instance in the HF and VHF bands (e.g. Koustov et al 2001Koustov et al , 2002Makarevitch et al 2001). However, in general, such approaches suffer from poor radar geometries and/or conflicting spatial and temporal resolutions.…”
Section: E-region Ionospheric Irregularitiesmentioning
confidence: 99%
“…They also found that Doppler velocities of FB irregularities in the E-region are limited to a value near the ion acoustic velocity. Recently, Koustov et al (2002) noted that in the EISCAT flux tube the STARE radars cannot always see a purely orthogonal backscatter, i.e. they suggested that a deficiency of the velocity measurements can be contaminated partly due to this fact.…”
Section: Discussionmentioning
confidence: 99%
“…The west-east asymmetry in STARE echo intensities is well known (see, e.g. by Koustov et al, 2002, their Fig. 4; Uspensky et al, 2003, their Fig.…”
Section: Features Of Data and Wave-wave Couplingmentioning
confidence: 99%
See 1 more Smart Citation